2015
DOI: 10.1542/peds.2015-1430
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Polycystic Ovary Syndrome in Adolescents

Abstract: Consensus has recently been reached by international pediatric subspecialty societies that otherwise unexplained persistent hyperandrogenic anovulation using age-and stage-appropriate standards are appropriate diagnostic criteria for polycystic ovary syndrome (PCOS) in adolescents. The purpose of this review is to summarize these recommendations and discuss their basis and implications. Anovulation is indicated by abnormal uterine bleeding, which exists when menstrual cycle length is outside the normal range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
122
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 94 publications
0
122
0
10
Order By: Relevance
“…In vitro fertilization studies found that PCOS patients have a lower oocyte implantation rate [32][33][34], due to oocytes which are exposed to high levels of androgens and other factors of abnormal levels, such as high insulin levels [3]. Gene chip analysis showed that abnormal endocrine and metabolic have a effects on the gene expression in PCOS oocyte, and most of the differentially expressed genes were upregulated in oocytes of PCOS patients [28,29,35].…”
Section: Ovarian Dysfunctionmentioning
confidence: 99%
“…In vitro fertilization studies found that PCOS patients have a lower oocyte implantation rate [32][33][34], due to oocytes which are exposed to high levels of androgens and other factors of abnormal levels, such as high insulin levels [3]. Gene chip analysis showed that abnormal endocrine and metabolic have a effects on the gene expression in PCOS oocyte, and most of the differentially expressed genes were upregulated in oocytes of PCOS patients [28,29,35].…”
Section: Ovarian Dysfunctionmentioning
confidence: 99%
“…So this condition is very important. [1][2][3][4][5][6] It is known that PCOS is not characterized by the association of hyperandrogenism and chronic anovulation only, but also involves disorders of carbohydrate metabolism, with a focus on insulin resistance and increased risk of developing diabetes. The latter is higher with increases in weight and ultimately the appearance of obesity, leading to dyslipidemia, metabolic syndrome and increased possibility of malignancies such as endometrial carcinoma.…”
mentioning
confidence: 99%
“…The latter is higher with increases in weight and ultimately the appearance of obesity, leading to dyslipidemia, metabolic syndrome and increased possibility of malignancies such as endometrial carcinoma. [1][2][3][4][5][6] Although the description of the clinical picture had been reported in the literature before the twentieth century, this syndrome was recognized by the work of two American surgeons, Stein e Leventhal, in 1935. 1 Since then, several publications have been made looking for a single agent to justify PCOS.…”
mentioning
confidence: 99%
See 2 more Smart Citations